Glimpse into the past: Analyses of the middle and inner ear of extinct rodents (Eusciurida; Rodentia; Mammalia) with implications for their locomotory behaviour - Cathrin Pfaff; Irina Ruf; Anne Le Maître (Palaeobiodiversity and Palaeoenvironments, 2026)
Rodentia is the most diverse and species-rich group of mammals, inhabiting almost all regions and ecosystems on earth. One of the most specialised subgroups is the Eusciurida, composed of Sciuridae, Gliridae, and Aplodontia rufa , and characterised by arboreal, fossorial and gliding taxa. Locomotion type not only influences postcranial morphology, but it is also known to be reflected in the shape of the vestibular system of the inner ear, which houses the sensory receptors for balance. Our extant sample comprises eusciurids (33 Sciuridae and seven Gliridae), as well as representatives of different groups of living mammals selected for their ecotypes similar to eusciurids: dermopterans ( Cynocephalus volans ), anomalurids ( Anomalurops beecrofti ), murids ( Rattus norvegicus) , treeshrews ( Tupaia sp.), and marsupials ( Petaurus breviceps papuanus ). The aim was to elucidate these ecotypes in fossil representatives of rodents. Multivariate analyses of three-dimensional linear and angular measurements of the vestibular system and the cochlea, as well as the volume of the different parts of the inner and middle ear were carried out. The cross-sectional diameter of the semicircular canals clearly distinguished fossorial from arboreal and gliding taxa, the latter being characterised by slender semicircular canals relative to their radius. We did not find any adaptive signal in the semicircular canal radius itself. In addition, our data show that fossorial taxa tend to have (i) a narrower angle between the posterior semicircular canal and each of the two other semicircular canals, (ii) a narrower anterior semicircular canal, and (iii) a higher number of cochlear turns, relative to gliders and arboreal species, at least within sciurids. Within this clade, fossorial taxa had larger volumes (after correction for skull length) for the vestibule of the inner ear and for the middle ear ossicles, compared to arboreal taxa. Based on our analysis of the lifestyles of extant taxa, we propose that early diverging rodents and sciurids were mainly fossorial and that they adapted later to an arboreal lifestyle. In such a scenario, gliding behaviour probably evolved just recently and only once within arboreal taxa.